Evaluating and analyzing student labor literacy in China's higher vocational education: an assessment model approach - Wu, Suhan; Duan, Jingyi; Luo, Min (Frontiers in Education, 2024)
This study introduces a novel methodology for evaluating labor literacy in China's higher vocational education, filling a critical gap in understanding vocational students' development of essential labor competencies. Employing an integrated approach, it combines a detailed questionnaire survey, rigorous econometric analysis, and the Delphi method to scrutinize labor literacy among 749 students from three prominent vocational institutions. Central to the research is the development of a pioneering labor literacy assessment model, mathematically denoted as S=0.5466B_1+0.1816B_2+0.1623B_3+0.1095B_4, S represents the overall labor literacy score and B_1, B_2, B_3, and B_4 correspond to the dimensions of labor concepts, habits and qualities, knowledge and skills, and emotions and attitudes. Empirical findings reveal significant disparities in labor literacy across these dimensions, particularly in labor concepts, and identify six determinants—gender, political profile, academic performance, internship and training base utilization, inclination towards innovation and entrepreneurship, and labor education evaluation mechanisms—that significantly influence labor literacy. This study's contributions transcend the assessment model, offering deep insights into labor literacy within China's socio-cultural context and providing actionable recommendations for educational strategies. It emphasizes the need for a holistic and context-aware approach to labor literacy, aligning with both educational objectives and labor market demands, thus advancing theoretical discourse in vocational education and serving as a vital guide for practitioners and policymakers.